Vagus nerve stimulation reduces cocaine seeking and alters plasticity in the extinction network - Childs, Jessica E. (Learn Mem, 2017)
Drugs of abuse cause changes in the prefrontal cortex (PFC) and associated regions that impair inhibitory control over drug-seeking. Breaking the contingencies between drug-associated cues and the delivery of the reward during extinction learning reduces rates of relapse. Here we used vagus nerve stimulation (VNS) to induce targeted synaptic plasticity to facilitate extinction of appetitive behaviors and to reduce relapse. Rats self-administered cocaine and were given VNS during extinction. Relapse to drug-seeking was assessed in a cued reinstatement session. We used immunohistochemistry to measure changes in the expression of the phosphorylated transcription factor cAMP response-element binding protein (pCREB) in the PFC and the basolateral amygdala (BLA), which regulate cue learning and extinction. In vivo recordings of evoked field potentials measured drug- and VNS-induced changes in metaplasticity in the pathway from the PFC to the BLA. VNS-treated rats showed improved rates of extinction and reduced reinstatement. Following reinstatement, pCREB levels were reduced in the IL and BLA of VNS-treated rats. Evoked responses in the BLA were greatly reduced in VNS-treated rats, and these rats were also resistant to the induction of LTD. Taken together, these results show that VNS facilitates extinction and reduces reinstatement. Changes in the pathway between the PFC and the amygdala may contribute to these beneficial effects.